Racial status and index of hive (Apis mellifera L.) infestation by Varroa destructor (Anderson and Trueman) in Mayabeque, Cuba - Pérez, Anisley; Demedio, J. (Cuban Journal of Agricultural Science, 2017)
In order to evaluate the racial status and index of hive infestation (Apis mellifera L.) and infestation rates of Varroa destructor in adult bees, important phenotypic and genotypic traits of the honeybee were evaluated in the Centro de Cría de Abejas Reinas (CCR) in Mayabeque, Cuba. For this purpose, the coloration of worker bee samples was determined according to yellow, intermediate and black scale. Using the fixed rule method, a biometric study of workers from these same hives and the diameter of cell for workers was carried out and infestation rates of Varroa destructor were evaluated. The variables coloration, length of the right forewing and diameter of the worker cells, together with the usual defensive behavior, indicated that the phenomenon of Africanization is not present in the studied hives. Taking studies of the 80s as a reference, there is a reduction of the forewing and a blackening of these bees as a result of being subjected to a selection process for "tolerance to Varroa", developed by humans and the influence of nature. This last characteristic comes, obviously, from the most ancient original breed Apis mellifera mellifera. Evaluated traits and infestation rates of Varroa, which showed values over 5 %, correspond to those of European breeds that gave origin to the current Cuban bee. Key words: Apis mellifera, racial status, varroosis, Africanization